Clinical manifestations and treatment outcomes in degos disease: a systematic review. (16th May 2021) - Kim, P.J.; Lytvyn, Y.; Kashetsky, N.; Bagit, A.; Mufti, A.; Yeung, J.
Abstract: Degos disease (atrophic papulosis) is a rare vasculopathy with cutaneous and systemic manifestations. Although potentially fatal, the characteristics of and treatments for Degos disease variants are not adequately described. We conducted a systematic review to summarize cutaneous and systemic presentations, treatments and outcomes of malignant (MAP) and benign (BAP) variants of Degos disease. A comprehensive search was conducted on Embase, MEDLINE, CINAHL and CENTRAL on 27 October 2020, which yielded 254 original studies reporting cases of Degos disease. A total of 357 patients were included in the analysis. Mean age of onset was 33.9 years. MAP was most commonly reported (63.8%, n = 228/357), with 56.6% (n = 129/228) mortality. Cutaneous lesions were usually asymptomatic (26.3%, n = 81/308) and localized to the trunk (57.7%, n = 206/357) and extremities (56.8%, n = 203/357). Systemic involvement developed within 2 years on average, ranging from 0 to 28 years. Anti‐platelet monotherapy had a complete resolution rate of 42.3% (n = 11/26) in BAP and 20.0% (n = 7/35) in MAP. Based on the findings of the study, most cases of Degos disease are malignant with high mortality, and even benign cutaneous cases may develop systemic disease in as late as 28 years. Anti‐platelet monotherapies may prove effective against both variants. Further studies are needed to confirm these findings.